2012
DOI: 10.1007/s00338-012-0919-7
|View full text |Cite
|
Sign up to set email alerts
|

Tissue loss in corals infested by acoelomorph flatworms (Waminoa sp.)

Abstract: Tissue loss in corals infested by acoelomorph flatworms (Waminoa sp.) Little is known about species and host specificity of epizoic acoelomorphs that live in association with corals (Barneah et al. 2012; Hoeksema et al. 2012). Most records concern zooxanthellate acoels of the genus Waminoa Winsor, 1990, which reproduce both sexually and asexually and may harm their hosts by shading and by eating their protective mucus layer, but no coral injuries have been reported so far (Haapkylä et al. 2009; Naumann et al. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 4 publications
2
16
0
3
Order By: Relevance
“…In this instance, only Waminoa sp. were observed, supporting a recent study which showed the presence of these species infesting mushroom corals in the same region, the Lembeh strait (Hoeksema & Farenzena, 2012). The effect these flatworms have on corals specifically when high infestations occur remains unknown.…”
Section: Discussionsupporting
confidence: 90%
“…In this instance, only Waminoa sp. were observed, supporting a recent study which showed the presence of these species infesting mushroom corals in the same region, the Lembeh strait (Hoeksema & Farenzena, 2012). The effect these flatworms have on corals specifically when high infestations occur remains unknown.…”
Section: Discussionsupporting
confidence: 90%
“…Unlike endolithic molluscs Kleemann and Hoeksema, 2002;Mas-sin, 1989Mas-sin, , 2000Massin and Dupont, 2003;Owada and Hoeksema, 2011) ectoparasitic epitoniids do not inflict serious visible damage to their host corals, as for instance seen in infestations by flatworms (Hoeksema and Farenzena, 2012). The mucus layer secreted by mushroom corals may be a means to protect their soft tissue against damage and is believed to be nutritious for other animals (Krupp, 1982(Krupp, , 1984(Krupp, , 1985Drollet et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Recent field evidence suggests that Waminoa spp. indeed cause significant tissue loss in scleractinian corals, possibly through impairment of host respiration, feeding and sediment shedding capacities (Hoeksema and Farenzena, 2012). …”
Section: Discussionmentioning
confidence: 99%